Implementation of Prudential Principles in Consumptive Credit Agreements (Study at Astra Credit Companies (Acc) Bengkulu City) - Karina Rizki Lestari; Hurairah Hurairah; Widya Timur (JURNAL HUKUM SEHASEN, 2022)
This study aims to understand how the Implementation of Prudential Principles in the Consumptive Credit Agreement Study of Astra Credit Companies (Acc) Bengkulu City. The research method that will be used in this research is normative research combined with field research in the form of interviews and field documentation (empirical), which is a way to obtain data from library materials, especially those related to legal issues. Implementation of the precautionary principle in credit agreements at Pt Acc Finance Bengkulu City The obligation to prepare and implement credit is applied by the stipulation of a written policy regarding credit and credit agreements.